Toxicological evaluation of tannery industry waste water on Oreochromis mossambicus - P. S. Navaraj; J. Yasmin (African Journal of Environmental Economics and Management, 2021)
This paper investigates the impact of tannery industry wastewater on O. mossambicus. The histopathological changes observed in gills, liver, kidney and brain of the studied fish have demonstrated the quality status of industrial waste water. In the vital organs, the following marked changes were observed: filament cell proliferation, cellular infiltration, haemorrhage and epithelial lifting in gills, vacuolation of hepatocytes and necrosis in liver, exfoliation and swollen with pyknotic nuclei in kidney and enlarged pyramidal cells, binucleated nuclei, vacuolation, and necrosis in brain. These changes might be due to the various components of tannery wastewater on fish. Hence, proper treatment of tannery industry wastewater is highly recommended through this study.